Theory of Audit Development: Dilemma «Principles and Rules» - Воронко, Р. М.; Редченко, К. І. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
The aim of this study is to determine the professional auditing principles and to develop a scientific approach to principles-base auditing. The ways of solving scientific dilemma «principles or rules» in the auditing sphere under conditions of the corporate reporting development are examined. The contradiction between the growth of the formalization of the audit and its tendency to intellectualization is revealed. At the beginning of XXI century the conflict between the concept of principles-based audit (liberal model) and the rules-based audit (prescriptive model) has reached the level of active debate in the scientific and professional environment. Based on the study we selected 15 professional auditing principles. We claimed that consistent observance of these principles is the key point to maintain the audit quality and its compliance with the expectations of stakeholders. Some of principles were straightforward, but others required a more detailed explanation and interpretation due to frequent changes (e.g., liability of auditors to detect fraud). For the realization of the modern concept of principles-based auditing we defined following assumptions: 1) professional auditing principles must be formulated clearly and unambiguously and the auditors must adhere them in practice consistently; 2) there is a reasonable balance between the general statements (principles) and specific requirements and procedures contained in the regulations and auditing standards; 3) the auditor’s judgment retains priority in matters relating to creating value for the company’s stakeholders.